Bioprinting: uncovering the utility layer-by-layer. Issue 3 (July 2017) - Burke, Madeline; Carter, Benjamin M; Perriman, Adam W
Bioprinting is becoming a must have capability in tissue engineering research. Key to the growth of the field is the inherent flexibility, which can be used to answer basic scientific questions that can only be addressed under 3D culture conditions, or organ-on-chip systems that could quickly replace underperforming animal models. Almost certainly the most challenging application of bioprinting will be for bottom-up tissue construction, which faces many of the same challenges as scaffold-based tissue engineering. In this review, the current state-of-the-art approaches to 3D bioprinting are discussed in terms of performance and suitability. This is complemented by an overview of hydrogel-based bioinks, with a special emphasis on composite biomaterial systems.